Here is your answer
12m-6
REASON:
6(2m-1)
Multiply 6 with both the terms in bracket, we get
6×2m - 6×1
= 12m-6
HOPE IT IS USEFUL
Answer: Irrational
Step-by-step explanation:
A-2: Project D.
b: Project A.
Not sure about a-1, hope I helped.
Answer:
D
Triangle Midsegment
5
10
Step-by-step explanation:
Got it right on the assignment on EDG2020 :)
A square has 4 equal sides
use pythagroeas theorem since a square has 4 right angles
a^2+b^2=c^2
a=b because the sides are equal (11)
11^2+11^2=c^2
242=c^2
square root both sides
11√2=c
the diagonal legnth is 11√2 centimiters